Peripheral expression of NPY1R-based heteroreceptor complexes reflects hippocampal neuroimmune status: Novel biomarkers for early Alzheimer’s disease detection. - Moreno-Madrid, Isabel; Romero-Imbroda, Jesús; Reyes-Bueno, José Antonio; Arrabal-Gómez, José Carlos; Díaz-Casares, Amelia; Díaz-Sánchez, Estela; Barbancho-Fernández, Miguel Ángel; Fuxe, Kjell; Borroto Escuela, Dasiel Óscar; Serrano-Castro, Pedro Jesús; Narváez-Peláez, Manuel (Elsevier, 2025)
Alzheimer’s disease (AD) evolves from a prodromal phase with subtle neuroimmune disturbances to overt cognitive decline and hippocampal neurodegeneration. Detecting these early changes non-invasively remains a critical unmet need. Here we show that the abundance of neuropeptide-Y receptor-type-1 (NPY1R)–based heteroreceptor complexes(NPY1R–GALR2 and NPY1R–TrkB), quantified by proximity ligation assay (PLA), constitutes a peripheral read-out of hippocampal status across two complementary rat models. In an acute AccellsiRNA model that selectively knocked down NPY1R in the cerebroventricular space (8 days post-injection), both heterocomplexes were markedly reduced in the dentate gyrus and in circulating white-blood cells (WBCs), yet hippocampal neurogenesis (doublecortin⁺ cells) and object-in-place memory were still preserved, mimicking the pre-symptomatic/mild cognitive-impairment (MCI) stage of AD. Conversely, in a bilateral olfactory bulbectomy (OBX) model that reproduces chronic AD-like pathology (2 weeks post-surgery), the same heteroreceptor complexes were diminished centrally and peripherally, and this loss co-occurred with impaired object-in-place performance and a 25 % decrease in dentate gyrus neurogenesis. These findings demonstrate that peripheral NPY1R-based heteroreceptor levels mirror hippocampal neuroimmune alterations both before and after the emergence of cognitive and neurogenic deficits. A blood-based PLA assay targeting these complexes could therefore enable ultra-early AD screening, monitor disease progression, and guide the timely initiation of disease-modifying therapies.
Keywords: Alzheimer, Enfermedad de; Neuropéptidos; Marcadores bioquímicos; Hipocampo (Cerebro); Neuroinmunología; Neuropeptide Y receptor type 1Heteroreceptor complexes; Alzheimer's disease biomarkers; Hippocampal neuroimmune status; Peripheral biomarkers; SiRNA mediated knockdown